The Effect of Mudharabah and Musyarakah Financing on the Capital Structure of Indonesian Islamic Banks during the Covid 19 Pandemic - Fadilla Fadilla; Choiriyah Choiriyah (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
This study was conducted to determine the effect of Mudharabah and Murabahah financing on the capital structure (Debt Ratio) at Indonesian Islamic Banks during the Covid 19 Pandemic. The research method used in this study was multiple linear regression analysis. There are two independent variables in this study, mudharaba as X1 and murabahah as X2, while the independent variable in this study is the capital structure proxied by the debt ratio. This research results show that Mudharabah and Murabahah financing are proven to have a simultaneous effect on the debt ratio because the ANOVA table significance test is 0.003. This value is smaller than 0.05. While partially mudharabah financing affects the debt ratio, Murabaha does not significantly affect the debt ratio.Keywords: Mudharabah Financing, Murabahah Financing, Debt Ratio Abstrak Penelitian ini dilakukan utuk mengetahui pengaruh pembiayaan Mudharabah dan Murabahah terhadap Struktur modal (Debt Ratio) pada Bank Syariah Indonesia pada masa Pandemi Covid 19. Metode penelitian yang dipakai dalam penelitian ini adalah analisis regresi linier berganda. Variabel independen penelitian ini ada dua yaitu mudharabah sebagai X1 dan murabahah sebagai X2, sedangkan variabel independen dalam penelitian ini adalah struktur modal yang di proxi dengan Debt ratio. Hasil dari peenelitian ini adalah pembiayaan Mudharabah dan Murabahah terbukti berpengaruh secara simultan terhadap Debt ratio, karena uji signifikansi tabel anova 0,003, nilai ini lebih kecil dari pada 0,05. Sedangkan secara parsial pembiayaan mudharabah berpengaruh terhadap Debt ratio sedangkan Murabahah tidak berpengaruh secara signifikan terhadap debt ratio.Kata Kunci : Pembiayaan Mudharabah, Pembiayaan Murabahah, Debt Ratio